Diversity: current and prospective secondary metabolites for nutrition and medicine - Sreenivasulu, Nese; Fernie, Alisdair R. (Elsevier, 2022)
Plants have been used as sources of food, feed and medicine for millennia. The ever-increasing population has, however, dramatically increased the burden on our arable land to meet nutritional demand. Concomitantly, and in part due to poor nutrition, we are faced with massive increases in chronic diseases, meaning the need for medicine has also increased. Here, we look back on research in these areas, surveying the polyphenols as a case study for health-conferring metabolites. We conclude that the tools that will allow us to breed more nutritious crops are all at hand. We stress that collaboration between plant and medical research needs to be intensified in order to improve our understanding of the bioactivities. In doing so, we attempt to draw a roadmap for the use of plants for mid-21st Century human health.